A LITERATURE REVIEW: THE POTENTIAL OF KARAMUNTING PLANT (Rhodomyrtus tomentosa) AS ANTIBACTERIAL AGENT - Gilang Ramadhan; Annisa Krisridwany; Andy Eko Wibowo; Muhammad Fariez Kurniawan; Vella Lailli Damarwati (Universitas Muhammadiyah Magelang, 2023)
Infectious disease is a major health problem with a relatively high mortality rate. Indonesia is rich in natural ingredients that have potential as antibacterials, one of which is the Karamunting plant (Rhodomyrtus tomentosa). Several studies on this plant have been conducted to observe its activity as an antibacterial. This study aims to determine the antibacterial activity of Karamunting plants using the literature review method. The literature search method uses journals from the Google Scholar, Pub Med and Elsevier databases. Each journal is determined based on inclusion and exclusion criteria. Journals that meet the inclusion criteria are descriptive and explained in detail. From the journals obtained, there were 11 journals that met the criteria. Karamunting plants (Rhodomyrtus tomentosa) contain secondary metabolites namely flavonoids, glycosides, saponins, tannins, triterpenoids, steroids, acylphloroglucinol (rhodomyrtone, tomentosone, rhodomyrtosone) and meroterpenoids (rhotomentodiones). Antibacterial activity test using the diffusion method showed an optimum inhibition zone diameter of 21.5 mm against Staphylococcus aureus bacteria in the ethyl acetate fraction of Karamunting leaves with a concentration of 600 mg/ml, while using the microdilution method of ethanol extract of Karamunting leaves the minimum inhibition level was 0.5 µg/ml on Staphylococcus aureus bacteria. The leaves’ part presents the best antibacterial activity.